MANAJEMEN INTERVENSI GIZI SEIMBANG PADA IBU HAMIL DAN IBU MENYUSUI UNTUK SUMBER DAYA MANUSIA BERKUALITAS BEBAS STUNTING - Arum Dwi Anjani; Indrayani , Indrayani; Rumengan, Angelina Eleonora; Devy Lestari Nurul Aulia (Jurnal Pendekar Nusantara, 2023)
The prevalence of stunting in Indonesia in 2022 is 21.3% (SSGI, 2022). In the Riau Islands Province, stunting cases in 2020 were 7.2%. Stunting results in a long-term decline in welfare for the nation. One indirect factor that has the potential to cause nutritional problems and stunting is knowledge. Rawa Jaya Village is a village located in Sugie Besar District, Niur Permai Health Center Working Area, Karimun Regency, the population's understanding of balanced nutrition, especially for pregnant women and breastfeeding mothers, is in the deficient category and there have still been cases of stunting in recent years. The objectives of this activity are: 1) Providing education about balanced nutrition for pregnant and breastfeeding mothers in preventing stunting, 2) Demonstration of processing katuk vegetables and Moringa leaves to increase nutrition and breast milk production. This Community Service Activity (PKM) was carried out at Polindes Rawa Jaya, in August 2023. The population of pregnant women and breastfeeding mothers was 11 people. PKM activities are carried out by providing education about balanced nutrition using leaflets as well as accompanying demonstrations on processing katuk vegetables and Moringa leaves to increase nutrition and breast milk production. The results of the activity showed an increase in knowledge of pregnant women and breastfeeding mothers after the management intervention provided education about balanced nutrition by 90%. It is hoped that this PKM activity will be able to motivate pregnant and breastfeeding mothers to implement balanced nutrition in making daily menus